Coaching for Breakthrough Success: Proven Techniques for Making Impossible Dreams Possible (Audio Book) - Canfield, Jack; Chee, Peter (McGraw-Hill, 2013)
A powerful new coaching method from Chicken Soup for the Soul co-creator Jack Canfield! "At the heart of a great coach is a firm belief that each player is a uniquely valuable individual with distinct giftedness and potential for greatness." That's the premise behind this brilliant empowering guide from Jack Canfield, coauthor of the 125 million-copy-selling Chicken Soup for the Soul series, and legendary global leadership development guru and CEO Dr. Peter Chee. Combining time-tested principles of exemplary coaches with the latest disruptive techniques used by the world's top performing leaders, this step-by-step playbook shows you how to nurture-in yourself and others-the three essential requirements of coaching excellence: 1. HEART: The Coaching Principles (TCP) unveils the secret to life impacting values, beliefs, and philosophies that permeate all aspects of great coaching. 2. MIND: The Situational Coaching Model (SCM) unleashes the genius of a coach to apply the right combination of crucial paradigms in any given coaching challenge. 3. ENERGY: The Achievers Coaching Techniques (ACT) equips you with proven methods that enable you to deliver breakthrough results in coaching. Coaching for Breakthrough Success is packed with stirring personal stories, life changing case studies, crucial coaching conversations, exemplary coaching questions, and ready-touse tools that equip you to achieve professional mastery in coaching. This practical manual guides you through the top 30 principles every coach needs to succeed. You'll learn the six paradigms of Situational Coaching, the ultimate power of Achievers Coaching Techniques, and the tried-and-true secret to making impossible dreams possible. All you need to lead your team to victory is heart, mind, energy-and Coaching for Breakthrough Success. Praise for Coaching for Breakthrough Success "Canfield and Chee have crafted the standard for anyone wanting to be an effective coach. Their actionable and timeless wisdom shows up through principles, questions, quotes, cases, and tools that will enable any aspiring coach to achieve their aspirations. Anyone being coached should make sure that their coach knows and follows these standards." -- Dave Ulrich, Professor, Ross School of Management, University of Michigan, Author of Leadership Sustainability "After years of working as an executive coach, I slowly came to the realization that knowing the answers to the tough questions wasn't as important as knowing ...